Mounting debts, less dividend payouts? The more loans companies have, the more dividends they pay - Guarino, Arthur; Wang, Wenjing (Archives of Business Research, 2020)
It has been a long-held principle in corporate finance that a company’s dividend payments must come from its net profits. Also, that the dividends paid to a company’s shareholders, whether holders of common or preferred stock, are entitled to some of those net profits in the form of dividends as a reward for investing and the risk involved. These concepts have been used in countless textbooks dealing with finance, accounting, and investments and has served as a basis for investors to purchase common or preferred stock throughout the decades. A company’s performance is often measured by how much dividends have increased over the years and whether it is a good long-term investment for individual investors, pension funds, mutual funds, and hedge funds. However, in recent years, the trend is changing in that corporations issuing common or preferred stock are paying dividends, not based on the amount of net profits they have made but based on the amount of financial capital that can be borrowed. A corporation may not necessarily make shareholders aware of this tactic as long as it adheres to its long-stated dividend policy and that they are receiving regular dividend payments whether they are increasing over time or remaining the same. The corporation could, in theory, maintain this method of paying dividends as long as the shareholders are satisfied and content with their cashflow from their equity investment in the company. But, in the long run, the corporation may actually be misleading shareholders as well as damaging the company’s financial situation by overextending itself with too much debt.